2019
DOI: 10.1371/journal.pone.0212893
|View full text |Cite
|
Sign up to set email alerts
|

Urea-mediated dissociation alleviate the false-positive Treponema pallidum-specific antibodies detected by ELISA

Abstract: The serological detection of antibodies to Treponema pallidum is essential to the diagnosis of syphilis. However, for the presence of cross-reaction, the specific antibody tests [e.g., enzyme-linked immunosorbent assay (ELISA)] always have false-positive results. In this study, we derived and validated the dissociation of urea in an attempt to alleviate the situation of false-positive antibodies to T . pallidum detected by ELISA. Six serum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The urea treatment was performed using sera from the rRT-PCR-positive controls, as well as the samples that had tested positive for IgM and/or IgG in either test. For the rapid test, the urea dissociation concentration (6 mol/L) and duration (25 min) were in line with previous studies ( Wang et al, 2019 , Wang et al, 2020 ); for ELISA, two different concentrations were tested in different wells: 4 mol/L, previously reported to be the best concentration ( Wang et al, 2020 ), and 6 mol/L. Results were expressed as the Affinity Index (AI) and interpreted according to the threshold values calculation method described by Wang et al (2020) .…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The urea treatment was performed using sera from the rRT-PCR-positive controls, as well as the samples that had tested positive for IgM and/or IgG in either test. For the rapid test, the urea dissociation concentration (6 mol/L) and duration (25 min) were in line with previous studies ( Wang et al, 2019 , Wang et al, 2020 ); for ELISA, two different concentrations were tested in different wells: 4 mol/L, previously reported to be the best concentration ( Wang et al, 2020 ), and 6 mol/L. Results were expressed as the Affinity Index (AI) and interpreted according to the threshold values calculation method described by Wang et al (2020) .…”
Section: Methodssupporting
confidence: 85%
“…The urea dissociation test, recently proposed by Wang et al, is based on the principle that urea dissociates the antigen-antibody reactions. The test has been used to evaluate the affinity of IgM and IgG for different pathogens ( Wang et al, 2019 , Wang et al, 2020 ). The urea treatment was performed using sera from the rRT-PCR-positive controls, as well as the samples that had tested positive for IgM and/or IgG in either test.…”
Section: Methodsmentioning
confidence: 99%
“…Both position papers were in favor of continuing administering biologic therapies to IBD patients as there is no evidence of increased risk associated with these drugs. Danese et al suggested the IBD Units may be reorganized in a way that the safety of IBD patients is guaranteed during the COVID-19 pandemic while they continue receiving all the necessary therapies for IBD [20] . In particular, the authors recommend establishing checkpoints at the hospital entrances to screen people with suspected upper respiratory symptoms, to allow entry only to patients without accompanying people, to investigate close contacts with confirmed or suspected COVID-19 infected patients, to respect social distancing during visits and therapy administration, and to use protective personal equipment (surgical masks and gloves) [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Urea is a type of dissociating agent that, functions to dissolve and denature protein. Previous studies in our laboratory have found that urea-mediated dissociation alleviates the false-positive Treponema pallidum -specific antibodies detected by ELISA 19 . However, whether urea-mediated dissociation can reduce the false-positive rate of the Elecsys HIV combi PT assay has not been studied.…”
Section: Introductionmentioning
confidence: 75%